False-positive antiglobulin tests in healthy subjects and in hospital patients. Issue 10 (October 1979) - Freedman, J
Abstract : An antiglobulin reagent containing anti-IgG, -C4c, -C4d, -C3c, and -C3d was used to test red blood cells from healthy subjects and from patients in hospital. In tests read macroscopically on opal tiles, no positive reactions were found in the healthy subjects. Positive reactions were, however, observed in 7% of the hospital patients. Further tests with monospecific reagents showed the positive reactions to be due to the presence of C4d and C3d on the red cells. All patients with positive antiglobulin reactions had serious disease, in most cases associated with abnormal antibody production or abnormal immunoglobulin levels.